Impact of c-JUN deficiency on thalamus development in mice and human neural models - Jiantao Shi; Qing Chen; Jianheng Lai; Jieying Zhu; Ran Zhang; Md. Abdul Mazid; Dongwei Li; Huanxing Su; Dajiang Qin (Cell & Bioscience)
Abstract Background c-Jun is a key regulator of gene expression. Through the formation of homo- or heterodimers, c-JUN binds to DNA and regulates gene transcription. While c-Jun plays a crucial role in embryonic development, its impact on nervous system development in higher mammals, especially for some deep structures, for example, thalamus in diencephalon, remains unclear. Methods To investigate the influence of c-JUN on early nervous system development, c-Jun knockout (KO) mice and c-JUN KO H1 embryonic stem cells (ESCs)-derived neural progenitor cells (NPCs), cerebral organoids (COs), and thalamus organoids (ThOs) models were used. We detected the dysplasia via histological examination and immunofluorescence staining, omics analysis, and loss/gain of function analysis. Results At embryonic day 14.5, c-Jun knockout (KO) mice exhibited sparseness of fibers in the brain ventricular parenchyma and malformation of the thalamus in the diencephalon. The absence of c-JUN accelerated the induction of NPCs but impaired the extension of fibers in human neuronal cultures. COs lacking c-JUN displayed a robust PAX6+/NESTIN+ exterior layer but lacked a fibers-connected core. Moreover, the subcortex-like areas exhibited defective thalamus characteristics with transcription factor 7 like 2-positive cells. Notably, in guided ThOs, c-JUN KO led to inadequate thalamus patterning with sparse internal nerve fibers. Chromatin accessibility analysis confirmed a less accessible chromatin state in genes related to the thalamus. Overexpression of c-JUN rescued these defects. RNA-seq identified 18 significantly down-regulated genes including RSPO2, WNT8B, MXRA5, HSPG2 and PLAGL1 while 24 genes including MSX1, CYP1B1, LMX1B, NQO1 and COL2A1 were significantly up-regulated. Conclusion Our findings from in vivo and in vitro experiments indicate that c-JUN depletion impedes the extension of nerve fibers and renders the thalamus susceptible to dysplasia during early mouse embryonic development and human ThO patterning. Our work provides evidence for the first time that c-JUN is a key transcription regulator that play important roles in the thalamus/diencephalon development.